Research progress on the application of Traditional Chinese Medicine five-element music therapy in lung cancer patients (中医五行音乐疗法在肺癌患者中的应用研究进展) - XIA Mengyang (夏梦阳); ZHANG Xiaohui (张晓辉); LI Tingting (李婷婷) (中西医结合护理)
Traditional Chinese Medicine five-element music therapy has been wildly used in prevention and adjuvant treatment of various diseases. This paper summarizes the concept and advantages of Traditional Chinese Medicine five-element music therapy, treatment mechanism, selecting music by syndrome differentiation and its application in lung cancer patients, in order to provide reference for promoting the physical, psychological and social health of lung cancer patients. (中医五行音乐疗法的临床应用包括治已病和治未病。本文从中医五行音乐的概念与优势、治疗机制、辨证施乐及其在肺癌患者中的应用进行综述, 以期加深医务人员对中医五行音乐疗法认知, 为今后制定针对各类癌症患者的个性化中医五行音乐治疗计划提供参考, 从而为肺癌患者提供更优质的护理服务。)